2022
DOI: 10.3389/fcvm.2022.932480
|View full text |Cite
|
Sign up to set email alerts
|

Novel Early Pregnancy Multimarker Screening Test for Preeclampsia Risk Prediction

Abstract: Preeclampsia (PE) is a common pregnancy-linked disease, causing preterm births, complicated deliveries, and health consequences for mothers and offspring. We have previously developed 6PLEX, a multiplex assay that measures PE-related maternal serum biomarkers ADAM12, sENG, leptin, PlGF, sFlt-1, and PTX3 in a single test tube. This study investigated the potential of 6PLEX to develop novel PE prediction models for early pregnancy. We analyzed 132 serum samples drawn at 70–275 gestational days (g days) from 53 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In particular, in the first trimester, the ADAM-12 concentrations were 79.1 ng/mL [69.1–98.5] in controls vs. 110.8 ng/mL [97.8–202.3] in women who developed PE [ 53 ]. This significant difference was not found in the third trimester [ 54 ]. This study seems not to confirm the results of Yu et al’s study in 2017, who demonstrated that a lower concentration of ADAM-12 was linked to an increased risk of developing PE [ 55 ].…”
Section: Protein Placental Biomarkersmentioning
confidence: 93%
“…In particular, in the first trimester, the ADAM-12 concentrations were 79.1 ng/mL [69.1–98.5] in controls vs. 110.8 ng/mL [97.8–202.3] in women who developed PE [ 53 ]. This significant difference was not found in the third trimester [ 54 ]. This study seems not to confirm the results of Yu et al’s study in 2017, who demonstrated that a lower concentration of ADAM-12 was linked to an increased risk of developing PE [ 55 ].…”
Section: Protein Placental Biomarkersmentioning
confidence: 93%
“…PE is highly heterogeneous due to the complex makeup of the maternalfetal interface and the varied and intricate patterns of interrelation between various cell types. [7][8][9] Therefore, there is no particularly effective, reliable, or economical way to forecast PE, 10,11 and the study of PE still faces a lot of challenges.…”
Section: Introductionmentioning
confidence: 99%